Gale Duality and the Neighborliness of Random Polytopes. II - A. G. Brodskiy (Моделирование и анализ информационных систем, 2015)
We have obtain of some distribution-independent results on the k-neighborliness of random polytopes. They confirm the well-known Gale conjecture for the general case.